1989
DOI: 10.5271/sjweh.1876
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to silica dust in the Danish stone industry.

Abstract: GUENEL P. BREUM NO. LYNGE E. Exposure to silica dust in the Dan ish sto ne ind ustry. Scand J Work Environ Health 1989; 15: 147-53. Expo sure 10 silica dust among Dan ish sto ne worke rs was assessed fro m data collected in . A rter I Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Exposure measurements were available from the Danish road and building material industry, and in the I970s the highest median exposure to respirable quartz was 0.29 mg/rn"; it was recorded for Bornholm. The work operations were not given in the employer records, and we were therefore not able to identify those who worked in the dusty crushing operations (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure measurements were available from the Danish road and building material industry, and in the I970s the highest median exposure to respirable quartz was 0.29 mg/rn"; it was recorded for Bornholm. The work operations were not given in the employer records, and we were therefore not able to identify those who worked in the dusty crushing operations (4).…”
Section: Discussionmentioning
confidence: 99%
“…These data were retrieved, and the analysis has been reported separately (4). The anal ysis showed the highest exposure levels to be found in the road and building material industry, where th e median exposure to respirable quartz in the 1970s was 0.16 (ran ge 0.02-1 2.7) mg/m', whereas the equi valent value for the stonecutting industry was 0.05 (range 0.02-0.57) mg/m' .…”
mentioning
confidence: 99%
“…Burns et al (1962) reported it as a danger among highway and dam construction rock drillers, Sacharov et al (1971) among slate quarry workers, Chernaik (1989) among tunnel construction rock drillers, and Guenel et al (1989) among rock quarry workers. Although rock drillers in underground coal mines have developed silicosis, those in surface coal mines have not historically been considered at significant risk (Fairman et al, 1977).…”
Section: Silicosis In Rock Drillersmentioning
confidence: 99%
“…Many of the processes involved have been associated with a number of occupational diseases, such as hearing loss and respiratory disorders. Several studies have reported increased exposures of marble workers to particulate matter, as well as exposures to heavy metals and crystalline silica, which is classified by IARC (1997) as a known human carcinogen (Scarselli et Guenel et al, 1989). The present study is the first effort to assess exposure to PM in the Greek marble processing sector.…”
Section: Introductionmentioning
confidence: 99%